Inefficient Foreign Borrowing: A Dual- and Common-Agency Perspective - Tirole, Jean (American Economic Review, 2003)
Studying the implications of uncoordinated borrowing, the paper first looks at whether and when countries borrow too much in the aggregate. It then revisits the “original sin” debate, analyzing whether and when equity portfolio investment, international portfolio diversification, domestic currency denomination and longer maturities enhance borrowing countries’ access to international lending. The paper thereby relates a country’s level and quality of access to international capital markets to a variety of institutional features such as the level of domestic savings, their location, the extent of control rights held by political authorities, and the interests of dominant domestic political forces.